Orthographic Variation in the Representation of Ingressive Plosives in Bimanese: Evidence from Digital Communication - Imansyah Imansyah (JUPE : Jurnal Pendidikan Mandala, 2026)
This study investigates the orthographic representation of the ingressive bilabial plosive /ƀ/ and the ingressive dental–epikopos plosive /đ/ in contemporary Bimanese (Bahasa Mbojo). Although these phonemes have been formally standardized in Kamus Mbojo–Indonesia Edisi Ketiga (2023), preliminary observations indicate significant variation in actual written usage. Drawing on naturally occurring data from WhatsApp group interactions among Bimanese speakers, this study identifies two dominant orthographic strategies: cluster substitution (ƀ → pb, đ → td) and phonological simplification (ƀ → b, đ → t). Using a qualitative-dominant mixed-method approach supported by phonological theory, acoustic phonetics, orthographic studies, and sociolinguistics, the study demonstrates that these forms are systematic and socially shared rather than random errors. The findings reveal a substantial gap between orthographic standardization and real-world language practice, shaped by phonological markedness, Indonesian language influence, and technological constraints in digital communication. This study contributes to broader discussions on orthography, language planning, phonological representation, and digital sociolinguistics in minority languages.